2017
DOI: 10.1097/mbc.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

The value and impact of anti-Xa activity monitoring for prophylactic dose adjustment of low-molecular-weight heparin during pregnancy

Abstract: : Low-molecular-weight heparin (LMWH) is the anticoagulant drug class of choice for the prevention of thrombosis during pregnancy and often used for prevention of severe obstetrical complications, yet the optimal dosage is still a matter of debate. Although several studies have evaluated LMWH dose adjustment methods based on anti-Xa levels, no definitive conclusion as yet exists. This extensive retrospective study sought to address the rationale of regular anti-Xa activity monitoring in pregnant patients given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
20
2
Order By: Relevance
“…Most reports support increasing LMWH dose as pregnancy progresses, and adjustments in LMWH dosing during pregnancy are recommended (Bates et al 2012; Swedish Society of Obstetrics and Gynecology (SFOG) and Working Group on Hemostatic Disorders (Hem-ARG) 2012; Royal College of Obstetricians and Gynaecologists 2015). Most requirements for dose adjustments are reported where the anticoagulant effect of LMWH is monitored by analyses of anti-FXa (Wahlberg and Kher 1994;Hunt et al 1997;Blomb€ ack et al 1998;Pettil€ a et al 1999;Schambeck et al 2001;Antovic et al 2002;Ulander et al 2002;Jacobsen et al 2003;Barbour et al 2004;Bauersachs et al 2007;Voke et al 2007;Lindqvist et al 2011;Schoenbeck et al 2011;Bj€ orgvinsdottir et al 2013;Revelj et al 2015;Boban et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most reports support increasing LMWH dose as pregnancy progresses, and adjustments in LMWH dosing during pregnancy are recommended (Bates et al 2012; Swedish Society of Obstetrics and Gynecology (SFOG) and Working Group on Hemostatic Disorders (Hem-ARG) 2012; Royal College of Obstetricians and Gynaecologists 2015). Most requirements for dose adjustments are reported where the anticoagulant effect of LMWH is monitored by analyses of anti-FXa (Wahlberg and Kher 1994;Hunt et al 1997;Blomb€ ack et al 1998;Pettil€ a et al 1999;Schambeck et al 2001;Antovic et al 2002;Ulander et al 2002;Jacobsen et al 2003;Barbour et al 2004;Bauersachs et al 2007;Voke et al 2007;Lindqvist et al 2011;Schoenbeck et al 2011;Bj€ orgvinsdottir et al 2013;Revelj et al 2015;Boban et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cost-effectiveness of monitoring all pregnant women taking LMWH should be considered after taking into account the potential complications and their expense. In previous studies investigating anti-FXa levels in pregnant women under LMWH prophylaxis, anti-FXa levels were not at the desired levels in a high percentage of patients [3,6]. In a recent study by Boban et al [3], 77 % of pregnant women under prophylactic LMWH treatment needed a dose increase.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies investigating anti-FXa levels in pregnant women under LMWH prophylaxis, anti-FXa levels were not at the desired levels in a high percentage of patients [3,6]. In a recent study by Boban et al [3], 77 % of pregnant women under prophylactic LMWH treatment needed a dose increase. Fox et al [6] reported that only 56 % of anti-FXa levels of pregnant women were in prophylactic range, whereas 29 % were sub-prophylactic.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations